2019
DOI: 10.5539/jmr.v11n2p20
|View full text |Cite
|
Sign up to set email alerts
|

Strong Geodetic Number in Some Networks

Abstract: A vertex subset S of a graph is called a strong geodetic set if there exists a choice of exactly one geodesic for each pair of vertices of S in such a way that these (|S| 2) geodesics cover all the vertices of graph G. The strong geodetic number of G, denoted by sg(G), is the smallest cardinality of a strong geodetic set. In this paper, we give an upper bound of strong geodetic number of the Cartesian product graphs and study this parameter for some Cartesian product networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Furthermore, Chartrand et al [11] showed that, for any connected graph G, g(G) ≤ n − diam(G) + 1, where dim(G) = max{d(u, v) : u, v ∈ V}. Several researchers have studied this topic and presented some results [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Chartrand et al [11] showed that, for any connected graph G, g(G) ≤ n − diam(G) + 1, where dim(G) = max{d(u, v) : u, v ∈ V}. Several researchers have studied this topic and presented some results [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…, n { }as i ∈ [n]. Some of the variants for covering the vertices problem are referred in [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Some results on strong geodetic problems can be referred in [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the variants for covering the vertices problem are referred in [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Some results on strong geodetic problems can be referred in [15][16][17][18][19]. A set S⊆V(G) is a geodetic set if it covers all the vertices of V(G)\S, and the cardinality of smallest geodetic set is called the geodetic number, denoted by g (G).…”
Section: Introductionmentioning
confidence: 99%